SOCIAL ASSISTANCE COMPREHENSION, IMPLEMENTATION, AND MONITORING IN PREVENTING SOCIAL ASSISTANCE CORRUPTION - Ananta, Geovani Dirga; Firnanda, Ongky Hikmal; Indradjaja, Nobella; Chamdani, Chamdani (SYNTIFIC, 2024)
Background. With widespread corruption cases in Indonesia regarding social assistance for the people in need, strict and transparent enforcement of justice is needed in facing various corruption crimes, not only for punitive or repressive purposes after the crime occurs but also for preventive purposes. This research aimed at the notion of and limitations of social assistance, implementation mechanism, as well as monitoring and accountability mechanism in distributing social assistance. Research Method. The method used in this research is normative legal research by observing positive law as primary resource material as well as literature from journals, books, and articles as secondary data. Findings. The current law in Indonesia has not clearly and comprehensively regulated updates on receiver data, has still implemented complicated procedures, and has not established a transparency mechanism to involve the public in monitoring the social assistance distribution. Conclusion. legal provisions that regulate these matters are necessary to minimize the opportunities for social assistance abuse to achieve social welfare for Indonesians.